Effects of Vegetation Patch Patterns on Channel Morphology: A Numerical Study. Issue 5 (13th May 2022) - Li, Jiaze; Claude, Nicolas; Tassi, Pablo; Cordier, Florian; Vargas‐Luna, Andrés; Crosato, Alessandra; Rodrigues, Stéphane
Abstract: This study investigates the effects of vegetation patch patterns on the morphological evolution of alluvial river channels at the reach‐scale. For this, a new two‐dimensional numerical biomorphodynamic model has been developed using the Telemac‐Mascaret system. Considering the newest development in the topic, the effects of vegetation on bedload transport are included by extending Einstein's parameters for the sediment transport formula. The model was subsequently validated by published laboratory experiments reproducing alternate bar dynamics with different vegetation establishment scenarios. The validated model was then used to study the influence of vegetation patch patterns on the channel morphological evolution considering the two most observed ones: (a) the filled pattern with plants well distributed within the patch, and (b) the stripe pattern with plants established only along the patch edges. 14 scenarios were simulated in total, including sensitivity analyses on the coefficients of vegetation characteristics. The results indicate that the morphological responses of an alternate bar system to the stripe pattern consist of channel widening, steeper slope and reduced water depth, with increased sediment transport rates. The effects of the filled pattern are similar but weaker. The results also show that with the stripe pattern, the alternate bars tend to migrate toward the centerline forming center bars. Besides, the scroll bars forming downstream are shorter, corresponding to less visible chute channels, compared to the filled pattern. Despite much less vegetation coverage, the stripe pattern decreases the bar elongation rates in a way similar to the filled pattern. Plain Language Summary: Vegetation influences river morphological evolution by reducing the flow velocity thus the sediment transport capacity of flowing water. Many studies have been carried out to investigate the influence of physical characteristics of uniformly distributed vegetation such as plant height, diameter, density, etc. However, the spatial distribution of vegetation in nature is generally presented as patches (an area of vegetation surrounded by bare soil) due to environmental factors. In this study, we developed a numerical model to investigate the effects of vegetation patch patterns on the channel morphological evolution considering the two most observed ones: (a) the filled pattern with plants well distributed within the patch, and (b) the stripe pattern with plants only aligned on the patch contour. The numerical results show that the channel morphological responses of two patch patterns present the same evolution tendency but with different rates. Besides, the stripe patch controls bar (an elevated region of sediment in the river) elongation rates, similar to the densely vegetated filled patch with the same contour line. This study provides new insights into the importance of the spatial distribution of vegetation for fluvial morphology evolution and helps to conceive river restoration management such as vegetation removal scenarios to remobilize vegetated river bars. Key Points: A numerical model considering the effects of vegetation on bedload sediment transport by extending Einstein's parameters is validated against laboratory experiments Morphological responses to filled and stripe patterns show similarities in chute channel formation and differences in reach‐scale channel characteristics Patches with plants located only along the patch edge control bar elongation similarly to densely vegetated patches at the same elevation